As ações do poder público no enfrentamento da exploração sexual infantojuvenil no município de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The present study aims to analyze the actions for combating sexual exploitation of children and youth by the Executive branch in the city of Manaus, in the period 2004/2010. Understood as a complex phenomenon and difficult to deal with and comes in defiance of society and the State to intervene in the pursuit of the rights of children and adolescents, sexual exploitation must be considered in its social aspects, cultural, political, legal and economic. It is a phenomenon that occurs on a global scale. In Brazil and particularly in the State of Amazonas is inserted in a context of deep social inequalities, economic, political and cultural. Therefore, sexual exploitation is a crime, as provided for in the Federal Constitution of 1988 and the Statute of children and adolescents is a serious social problem which is a strong violation of the rights of the child, is a matter that requires urgency in your face, needs the involvement and commitment of the actors and institutions involved in the defense of the rights of the population of children and youth so that's priority in the public agenda. In this sense, sought to identify the design management that pervades the work of executive power regarding the actions to counter sexual exploitation of children and youth in the city of Manaus; Learn about the programs and projects developed by the Executive power to fight sexual exploitation of children and youth and analyze the discourses of the professionals involved in the process of combating sexual exploitation of children and youth in the city of Manaus. This investigation is the need to verify what has been the response by the State on the violation of rights of children and adolescents, to do so it was necessary to select the institutions involved in this process in the city of Manaus. Thus, the data were collected through interviews with the subjects of research, survey reports and documents. The locus of research were the secretariats of the Municipal City Hall of Manaus, which correspond to the policies of health, Social assistance and education (SEMED, SEMSA and SEMASDH). This research is characterized by a qualitative approach where the universe of meanings, of reason, of the values and attitudes of the subject-object of study. The sample of this research configures itself as an intentional sample and 10 were selected subject, being professionals and managers. This research constitutes a way to recognize and analyze the existence of actions concerning the fight against sexual exploitation of children and youth in Manaus through the actions of the Executive Branch, so this recognition implies that there are actions of confrontation in the city of Manaus, as there are institutions and bodies that direct its dayto- day efforts in search of results in relation to combat sexual exploitation in the municipality. However, such actions are developed in isolation and disjointed and so does not configure the confrontation of this problematic in that municipality. To fight sexual exploitation of children and youth in the city of Manaus is necessary to think a public policy for childhood to guarantee the principles and guidelines set out in ECA and in the Federal Constitution as major legal parameters for the creation of programs, projects and services aimed at prevention and the protection of childhood, what it means to prevent this violation of rights occur. Therefore, it is concluded that the Executive branch does not prioritize the fight against sexual exploitation of children and youth shows flaws as their understanding and sizing your complexity. And by this lack of priority we want to point out the situation of children and adolescents who do not have their rights guaranteed in the city of Manaus.
Keywords: Exploração Sexual; Criança e Adolescente; Assistência a menores; Desigualdade social; Sexual exploitation; Child and adolescent; Assistance for minors; Social inequality; CIÊNCIAS SOCIAIS APLICADAS: SERVIÇO SOCIAL